2018
DOI: 10.1016/j.envint.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in assessing the health risks of consuming vegetables in metal-contaminated environments

Abstract: A great deal of research has been devoted to the characterization of metal exposure due to the consumption of vegetables from urban or industrialized areas. It may seem comforting that concentrations in crops, as well as estimated exposure levels, are often found to be below permissible limits. However, we show that even a moderate increase in metal accumulation in crops may result in a significant increase in exposure. We also highlight the importance of assessing exposure levels in relation to a regional bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The 95th percentiles of the HIs via vegetable consumption for children, adolescents, and adults were 15.71, 11.15, and 9.34, respectively, indicating potential risks for all age groups. Children were more vulnerable to dietary heavy metal intake, which may be ascribed to their higher metabolisms and absorption capacities compared with adolescents and adults [59].…”
Section: Resultsmentioning
confidence: 99%
“…The 95th percentiles of the HIs via vegetable consumption for children, adolescents, and adults were 15.71, 11.15, and 9.34, respectively, indicating potential risks for all age groups. Children were more vulnerable to dietary heavy metal intake, which may be ascribed to their higher metabolisms and absorption capacities compared with adolescents and adults [59].…”
Section: Resultsmentioning
confidence: 99%
“…These metals may be deposited on vegetables, fruit and berries as well as the residents, resulting in chronic exposure to low-level metal concentrations over a lifetime. Metal uptake in vegetables in areas with industrial emissions have been documented in several studies (Hellström et al 2007;Helmfrid et al 2007;Sundstrom & Jorhem 2008;Nyberg et al 2012;Uddh-Söderberg et al 2015;Dziubanek et al 2015;Yousaf et al 2016;Ur Rehman et al 2017;Augustsson et al 2018). Göransson (1983).…”
Section: Exposure To Contaminantsmentioning
confidence: 96%
“…In the glassworks area, elevated Cd and Pb concentrations in vegetables have been reported (Augustsson et al 2015;Uddh-Söderberg et al 2015;Augustsson et al 2018). It can thus be hypothesized that long-term consumption of local food from the contaminated areas may contribute to elevated body burdens of contaminants.…”
Section: Association Between Measured Levels Of Toxic Substances In Bmentioning
confidence: 99%
“…A potential exposure route for those residing in the study area is the consumption of contaminated food. A recent study from The Kingdom of Cristal [ 34 ] analyzed the levels of Cd, Pb and As in a range of vegetables grown and collected near 22 contaminated glasswork sites. Their results indicated that only levels of Pb were higher in vegetables from glasswork sites compared to those grown and harvested in reference areas.…”
Section: Introductionmentioning
confidence: 99%